EFEKTIVITAS PENERAPAN ATRAUMATIC CARE DENGAN MEDICAL PLAY DAN BERMAIN JENGA TERHADAP PENURUNAN KECEMASAN ANAK USIA 3-6 TAHUN SELAMA HOSPITALISASI DI RUMAH SAKIT HORAS INSANI PEMATANG SIANTAR - Purba, Eva Rosaulina; Dior Manta Tambunan (JOURNAL SAINS STUDENT RESEARCH, 2025)
Children are unique beings with different needs at each stage of their development. Therefore, parents need to understand the importance of providing facilities to support their growth and development. Children aged 3-6 years are in the preschool stage of development. During this period, children view illness as a punishment. Therefore, when a child is sick and hospitalized, it is the first crisis that must be understood by the child and can cause stress in the child. Hospitalization of children is a stressful experience, both for children and parents. The type of research used in this study is quantitative research. This type of research uses a quasi-experimental design with a two-group pre- and post-test. The purpose of this study is to analyze the differences in the effectiveness of Jenga play therapy and medical play therapy. The population in this study was all pediatric patients aged 3-6 years old treated in the Bougenvil and Teratai rooms on the 2nd floor of Horas Insani Hospital, Pematang Siantar, with an average of 35 patients in 3 months from October to December 2022. The sampling technique in this study was total sampling. There were 17 respondents in the Medical Play Group and 17 respondents in the Jenga Play Group. The instrument used in this study was a questionnaire. The data collection tool for anxiety in children used a modified Spence Children Anxiety Scale (SCAS) questionnaire for preschool-aged children. The questionnaire was completed by parents, including fathers, mothers, and caregivers who understood the child's condition. The Spence Children Anxiety Scale (SCAS) questionnaire, adopted from Ilmiasih (2012), consists of 26 questions and has been tested for validity and reliability by the researcher. The conclusion is that there is an effect of Medical Play on anxiety levels after the intervention through a Paired T-Test with a p-value of 0.000, and there is an effect of Jenga play on anxiety levels after the intervention through a Wilcoxon statistical test with a p-value of >0.000.